2018
DOI: 10.1584/jpestics.d17-079
|View full text |Cite
|
Sign up to set email alerts
|

Species differences in the developmental toxicity of procymidone—Placental transfer of procymidone in pregnant rats, rabbits, and monkeys—

Abstract: To clarify species differences in the developmental toxicity of procymidone (Sumilex ® , a fungicide for agricultural use), placental transfer studies were conducted using 14 C-labeled procymidone in pregnant rats, rabbits, and monkeys. These studies demonstrated that maternal-to-fetal transfer of the parent compound and its hydroxylated metabolite, which are both weak anti-androgenic agents, occurred more easily than that of other metabolites, with much higher absolute concentrations achieved in the fetal cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 22 publications
(34 reference statements)
1
18
0
Order By: Relevance
“…Pharmacokinetics, Metabolism, and Excretion Studies (Groups 1−4). After the quarantine period of over 2 days, 14 C-procymidone in corn oil was administered as the single oral dose at 37.5 mg/kg/10 mL (Groups 1 and 2, low dose) or 62.5 mg/kg/10 mL (Groups 3 and 4, high dose). The low dose (37.5 mg/kg) was the lowest toxicologically effective dose to present the developmental toxicity as confirmed in our laboratory and the high dose (62.5 mg/kg) was the toxicological effect level showing decreased spontaneous activity.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Pharmacokinetics, Metabolism, and Excretion Studies (Groups 1−4). After the quarantine period of over 2 days, 14 C-procymidone in corn oil was administered as the single oral dose at 37.5 mg/kg/10 mL (Groups 1 and 2, low dose) or 62.5 mg/kg/10 mL (Groups 3 and 4, high dose). The low dose (37.5 mg/kg) was the lowest toxicologically effective dose to present the developmental toxicity as confirmed in our laboratory and the high dose (62.5 mg/kg) was the toxicological effect level showing decreased spontaneous activity.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The mice were anesthetized (by intraperitoneal administration of a mixture of xylazine hydrochloride and ketamine hydrochloride) and gall bladders were cannulated with polyethylene tubes. After recovery from anesthesia, 14 C-procymidone was orally administered at 37.5 mg/kg to each mouse.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…3) The species difference in the maternal exposure to the hydroxylated metabolite results in a significant difference in fetal exposure. 4) From these results, it was suggested that the species difference in the developmental toxicity of procymidone is mainly due to variation in the level of exposure to the causal substance, hydroxylated metabolite, and this variation stems from interspecies differences in the biliary excretion route of the glucuronide. To assess the teratogenic risk associated with procymidone in humans, the excretion route and rate of formation of glucuronides, which are key factors involved in the mechanism of the toxicity must be clarified.…”
Section: Human Safety Assessment Of the Fungicide Procymidonementioning
confidence: 99%